Evaluasi Ekstensifikasi dan Intensifikasi Pajak Serta Kontribusinya dalam Meningkatkan Penerimaan Pajak Penghasilan Orang Pribadi pada KPP Pratama Jakarta Tanah Abang Dua - Maya Safira Dewi; Mirza Maulida (Binus Business Review, 2012)
In 2010, a number of efforts such as the safeguard mechanism has been implemented by the KPP Pratama Jakarta Tanah Abang Dua, one of the safeguard mechanism is an intensification of activity or potential tax starting from the unified tax mapping activities, benchmarking and profiling, with an analysis of the sectors found on the contribution of a region (eg county or city) or the sectors contained in the contribution of tax revenue a tax services office or regional office of the Directorate General of Taxes. Given the working area of KPP Pratama Jakarta Tanah Abang Dua are in the economic and strategic business centers and many residents which don’t have tax ID, provide more opportunity for KPP in capturing the public to serve the taxpayer by providing tax ID. But in actual KPP Pratama Jakarta Tanah Abang Dua should be able to read situations and anticipate the various circumstances that might be a problem in the smooth operation of extending the taxpayer, such as mutations in the population without changing the domicile of the candidate statements taxpayers of local authorities and social conditions change.